2008
DOI: 10.1016/j.jtcvs.2007.12.038
|View full text |Cite
|
Sign up to set email alerts
|

Endocardial hypothermia and pulmonary vein isolation with epicardial cryoablation in a porcine beating-heart model

Abstract: Epicardial cryoablation can produce long-term pulmonary vein isolation in a beating heart. Dose-response studies demonstrate consistent endocardial hypothermia in tissues up to 7 mm thick. To our knowledge, this is the first report documenting endocardial hypothermia during epicardial cryoablation. This technology holds promise for performing the complete maze procedure on a beating heart.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…Masroor et al . were able to produce transmural right ventricular lesions during epicardial freezing in pigs [125]. Kettering et al produced long linear lesions with a cryocatheter in pigs by using multiple points of application at −75°C for four minutes [104].…”
Section: Diverse Tissuementioning
confidence: 99%
“…Masroor et al . were able to produce transmural right ventricular lesions during epicardial freezing in pigs [125]. Kettering et al produced long linear lesions with a cryocatheter in pigs by using multiple points of application at −75°C for four minutes [104].…”
Section: Diverse Tissuementioning
confidence: 99%
“…4 , 13 18 As the use of cryotherapy continues to grow, improvements to device design and application will further increase its utilization for the treatment of cardiac arrhythmias. 4 12 , 19 , 20 …”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] A plethora of studies have detailed the use of various cryosurgical devices and procedures to apply freezing temperatures to a target tissue. [4][5][6][7][8][9][10][11][12] With the recent reports on the success of cryo for atrial fibrillation (AF) treatment, there is now increasing use of cryo as a standalone, minimally invasive procedure to treat many forms of cardiac arrhythmias. 4,[13][14][15][16][17][18] As the use of cryotherapy continues to grow, improvements to device design and application will further increase its utilization for the treatment of cardiac arrhythmias.…”
Section: Introductionmentioning
confidence: 99%
“…Wadhwa et al reported that successful transmurality was achieved with catheter cryoablation in the canine ventricle [38]. Masroor et al reported that endocardial hypothermia was achieved with epicardial cryoablation on a beating heart model in pigs [39]. Schill et al reported that the latest cryoablation probe produced transmural lesions in 97% of the arrested heart in an ovine model [40].…”
Section: Transmurality Of Cryoablationmentioning
confidence: 99%